Top 100 cited articles in cardiovascular magnetic resonance: a bibliometric analysis - Khan, Muhammad Shahzeb (J Cardiovasc Magn Reson, 2016)
BACKGROUND: With limited health care resources, bibliometric studies can help guide researchers and research funding agencies towards areas where reallocation or increase in research activity is warranted. Bibliometric analyses have been published in many specialties and sub-specialties but our literature search did not reveal a bibliometric analysis on Cardiovascular Magnetic Resonance (CMR). The main objective of the study was to identify the trends of the top 100 cited articles on CMR research. METHODS: Web of Science (WOS) search was used to create a database of all English language scientific journals. This search was then cross-referenced with a similar search term query of Scopus® to identify articles that may have been missed on the initial search. Articles were ranked by citation count and screened by two independent reviewers. RESULTS: Citations for the top 100 articles ranged from 178 to 1925 with a median of 319.5. Only 17 articles were cited more than 500 times, and the vast majority (n = 72) were cited between 200–499 times. More than half of the articles (n = 52) were from the United States of America, and more than one quarter (n = 21) from the United Kingdom. More than four fifth (n = 86) of the articles were published between the time period 2000–2014 with only 1 article published before 1990. Circulation and Journal of the American College of Cardiology made up more than half (n = 62) of the list. We found 10 authors who had greater than 5 publications in the list. CONCLUSION: Our study provides an insight on the characteristics and quality of the most highly cited CMR literature, and a list of the most influential references related to CMR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12968-016-0303-9) contains supplementary material, which is available to authorized users.